Effect of conditioner on microtensile bond strength of self-adhesive resin cements to dentin - Daniela Tonial (2022)
Submitted by Biblioteca Suporte PUCRS (biblioteca.suporte@pucrs.br) on 2022-05-25T14:35:26Z No. of bitstreams: 2 Effect_of_conditioner_on_microtensile_bond_strength_of_selfadhesive_resin_cements_to_dentin.pdf: 252843 bytes, checksum: 9e1d6c25685eedf1e4a1362c8e9fa13a (MD5) Effect_of_conditioner_on_microtensile_bond_strength_of_selfadhesive_resin_cements_to_dentin.pdf: 252843 bytes, checksum: 9e1d6c25685eedf1e4a1362c8e9fa13a (MD5)